TRANSVERSAL SKILLS THAT MATTER TO COMPUTER ENGINEERING AND INFORMATION TECHNOLOGY UNDERGRADUATES AND STRATEGIES FOR THEIR DEVELOPMENT IN ENGLISH CLASSROOM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The importance of transversal skills for employees who work in the field of computer science is undeniable as transversal skills complement technical computer science skills and play a key role in their professional development and success. It means that while studying at higher educational institutions Computer Engineering and Information Technology undergraduates should have all the opportunities to develop these skills. And the English language classroom is not an exception since English teachers can use a wide range of strategies for developing transversal skills among Computer Engineering and Information Technology undergraduates. The research is aimed at finding out Computer Engineering and Information Technology undergraduates’ points of view on the importance of transversal skills for their future work and identifying effective strategies for their development in the English language classroom. 217 Computer Engineering and Information Technology undergraduates were participants in the research conducted by the team of researchers. To find out Computer Engineering and Information Technology undergraduates’ points of view of the importance of transversal skills for their future work and to identify effective strategies for their developing in the English language classroom, the researchers developed a questionnaire which consisted of close-ended and open-ended questions and items on a 5-Likert scale. The study may contribute to the improvement of Computer Engineering and Information Technology undergraduates’ training by identifying effective strategies for the development of transversal skills in the English language classroom.